Lung ultrasound in the neonatal intensive care unit: Review of the literature and future perspectives. Issue 7 (27th April 2020) - Corsini, Iuri; Parri, Niccolò; Ficial, Benjamim; Dani, Carlo
Abstract: Lung ultrasound (LU) has been increasingly used as a point‐of‐care method in recent years. LU has numerous advantages compared to traditional imaging tools such as chest X‐ray (radiography) (CXR): it is faster and portable, does not use ionizing radiation, is performed by the same physician who cares for the patient, and can be repeated to follow the progress of the disease and the response to treatment. There is a large body of evidence that LU has an excellent diagnostic effectiveness compared to CXR, not only in adults and children, but also in neonates. This review article describes how to perform LU, how to interpret findings, and how to use LU to diagnose and differentiate common neonatal pulmonary diseases. Strengths but also limits of the technique are highlighted. Finally, we describe the recent revolutionary role of LU. The development of scoring methods in neonates with respiratory distress syndrome allowed to quantify the severity of the disease and to assist the physician in the clinical management and follow‐up.